PENGARUH HEDONIC SHOPPING MOTIVATION DAN PRICE DISCOUNT TERHADAP IMPULSE BUYING (STUDI PADA KARYAWAN SWASTA KONSUMEN STARBUCKS COFFEE - Dewi Andini Saputri; Widayanto Widayanto; Agung Budiatmo (Universitas Diponegoro, 2024)
The high consumption of coffee is in line with the growth of coffee shops in Indonesia. Starbucks is a coffee shop brand from the United States whose stores are spread across major cities in Indonesia include Semarang. Based on the Top Brand Index, Starbucks Coffee is in first place but the percentage is still fluctuating. One of the Top Brand Index parameters is the market share related to consumer purchases. The type of purchase that has a good impact on the company is impulse buying. The purpose of this study is to prove the effect of hedonic shopping motivation and price discounts on impulse buying. The type of research is explanatory research, samples taken using non-probability sampling with purposive sampling and accidental sampling. Data were collected from 97 respondents, after being valid and reliable then analyzed with correlation coefficients, determination coefficients, linear regression, t and F tests with SPSS version 26. The results of hedonic shopping motivation and price discount studies had a positive and significant effect on impulse buying both partially and simultaneous. Companies need to provide more attractive and trendy menus to make consumers happy, price discounts can be increased to attract consumers from the frequency of giving.Keywords: hedonic shopping motivation, impulse buying, price discountTingginya konsumsi kopi sejalan dengan pertumbuhan kedai kopi di Indonesia. Starbucks merupakan merek kedai kopi dari Amerika Serikat yang kedainya tersebar di kota besar Indonesia termasuk Semarang. Berdasarkan Top Brand Index, posisi Starbucks Coffee berada di urutan pertama namun persentase masih fluktuasi. Parameter Top Brand Index salah satunya market share yang berkaitan dengan pembelian konsumen. Jenis pembelian yang berdampak baik untuk perusahaan adalah impulse buying. Tujuan penelitian ini untuk membuktikan pengaruh hedonic shopping motivation dan price discount terhadap impulse buying. Tipe penelitiannya explanatory research, sampel yang diambil menggunakan non probability sampling dengan purposive sampling dan accidental sampling. Data dikumpulkan dari 97 responden, setelah valid dan reliabel kemudian dianalisis dengan koefisien korelasi, koefisien determinasi, regresi linear, uji t dan F dengan SPSS versi 26. Hasil penelitian hedonic shopping motivation dan price discount berpengaruh positif dan signifikan terhadap impulse buying baik secara parsial maupun simultan. Perusahaan perlu menyediakan menu lebih menarik dan trendy untuk membuat konsumen senang, price discount dapat ditingkatkan untuk menarik konsumen dari frekuensi pemberian.Kata Kunci : hedonic shopping motivation, impulse buying, price discount